Limiar de percepção sensorial da presença de grãos Quakers em café natural especial - Rabelo, Mariane Helena Sances (2016)
Global consumption of specialty coffees in 2015 was superior to eight million 60 kg bags, representing a consumer market in the order of 1.840 billion dollars per year, which corresponds to 32.7% of the total revenue of the coffee market. According to the American Association of Specialty Coffees (AASC), a sample of roasted coffee is classified as specialty when it presents, in addition to other criteria, the absence of immature grain, which did not develop during roasting, denominated Quaker. The highest incidence of Quaker is associated to the production of natural coffee, due to the influence of current technologies available. However, it is common to find natural coffees being commercialized as specialty when containing variable amounts of Quaker, leading to the questioning of whether the criteria adopted by the AASC is valid. In addition, there are no scientific evidence that prove the impact these grain have over sensorial quality, as well as which would be the limit of its perception. Thus, we aimed at determining the threshold value of perception and the possible impacts of the Quaker over specialty coffee from adaptations made to the AASC protocol. The study was conducted using natural Coffea arabica, produced in Brazil. For evaluating the presence and impacts of the Quaker, we created three grain categories based on the Agtron coloring system. For category Agtron 61, 0 to 30 grain/cup were used, and for Agtron 82 and Agtron 95, 0 to 16 grain/cup were used. The sensorial evaluation was conducted by five tasters with Q-Grader certification. Adaptations were made to the sensorial evaluation sheet in order to promote the better description of the attributed and characteristics of the beverage. Based on the results, Agtron 82 and 95 have significant influence over the quality of specialty natural coffee, providing a marked flavor of immature coffee. The perception of prejudicial effects becomes evident with 7 grain, directly affecting global grade, sweetness, astringency and finishing.